Modified PET / SPECT cylindrical phantom - Sayed, Inayatullah Shah; Shah, Ayaz Ali (Springer Berlin Heidelberg, 2007)
It is mandatory to assess / evaluate performance parameters of all medical imaging systems employed in diagnostic imaging modalities before their use in patient studies. For such evaluations a number of commercially available test phantoms exist, e.g., in nuclear medicine tomography - PET/SPECT phantoms. A cylindrical PET/SPECT phantom (R A Carlson) which consists of hot, cold and linearity inserts has been modified. An additional pair of holes 30 mm diameter (hot regions in a cold background) — including “V” shaped eight pairs of various sized holes — near the edges to the hot regions insert opposite to each other at 180° from the centre of the insert is drilled. For cold regions insert, solid plastic rods 5 cm long (each) with same diameters and exactly the same arrangement as hot region holes pairs is designed. Both inserts have been attached with each other by aligning hot and cold regions for same cross sectional views. The data acquired by this arrangement provides a simple way for measurement and comparison of the performance of a system i.e., image resolution in terms of positions of hot and cold regions in the phantom, lesion detectability. Also the accuracy of scatter and attenuation correction techniques in nuclear medicine tomography may be tested.